Free-choice feeding of shelled corn and a protein mixed supplement compared with feeding pigs completely mixed rations in pellet form. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment consisted of two lots of nine pigs each. Lot 1 pigs were fed free-choice shelled corn and a mixed protein supplement made up of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. The supplement had a crude protein percentage of 49. Lot 2 pigs were fed pellets of corn ground and mixed with the same protein supplement at the ratio of 3 ½ parts corn to 1 part supplement. This was fed from 50 pounds, their starting weight, to 75 pounds. The 3 ½ -to-1 pellet had a protein percentage of 19.06. At 75 pounds the ratio of corn to protein supplement was changed to 6 to 1 and fed until the pigs reached 125 pounds. This pellet tested 16.9 percent protein. From 125 pounds to finish the pigs received a pellet with corn to supplement ratio of 9 to 1, which had a protein percentage of 14.3. No antibiotic was fed to either lot.
Keywords: Swine; Corn; Protein; Gain